2020
DOI: 10.2967/jnumed.119.234542
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Optical Imaging of the Glucagonlike Peptide 1 Receptor Using Exendin-4-IRDye 800CW

Abstract: The treatment of choice for insulinomas and focal lesions in congenital hyperinsulinism (CHI) is surgery. However, intra-operative detection can be challenging. This could be overcome with intraoperative fluorescence imaging, which provides real-time lesion detection with a high spatial resolution. Here, a novel method for targeted near-infrared (NIR) fluorescence imaging of glucagon-like peptide 1 receptor (GLP-1R) positive lesions, using the GLP-1 agonist exendin-4, labeled with IRDye800CW, was examined in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…GLP-1 appears to mildly reduce action potentials in the alpha cell membrane at 1 mM glucose in isolated mouse alpha cells, and this effect is blocked by the GLP-1R antagonist exendin (9-39) ( 110 ), therefore suggesting the presence of GLP-1R, perhaps at a very low density, on a small proportion of alpha cells. The development of near infra-red and fluorescent analogues of GLP-1R ligands has enabled both in vivo ( 111 , 112 ) and high-resolution tissue imaging ( 113 , 114 ) of GLP-1R with high specificity, sensitivity, and reproducibility. Coupled with super-resolution microscopy, the fluorescent analog LUXendin645 revealed that 5% of alpha cells in murine islets expressed GLP-1R ( 114 ).…”
Section: Role Of Glp-1: Intra-islet or Intestinal?mentioning
confidence: 99%
“…GLP-1 appears to mildly reduce action potentials in the alpha cell membrane at 1 mM glucose in isolated mouse alpha cells, and this effect is blocked by the GLP-1R antagonist exendin (9-39) ( 110 ), therefore suggesting the presence of GLP-1R, perhaps at a very low density, on a small proportion of alpha cells. The development of near infra-red and fluorescent analogues of GLP-1R ligands has enabled both in vivo ( 111 , 112 ) and high-resolution tissue imaging ( 113 , 114 ) of GLP-1R with high specificity, sensitivity, and reproducibility. Coupled with super-resolution microscopy, the fluorescent analog LUXendin645 revealed that 5% of alpha cells in murine islets expressed GLP-1R ( 114 ).…”
Section: Role Of Glp-1: Intra-islet or Intestinal?mentioning
confidence: 99%
“…[67][68][69] We have developed a clinical grade exendin-4-IRDye800CW conjugate and shown feasibility of insulinoma targeting and imaging in mice with subcutaneous GLP-1R overexpressing Chinese hamster lung cell tumors. 70 We intent to start clinical trials in which this tracer is employed for FGS of insulinoma. To combine high resolution, high sensitivity, and deep tissue penetration, dual-labeled targeting moieties with a radionuclide and fluorophore have been developed for other theranostic applications in oncology.…”
Section: Fluorescence Imaging For Intraoperative Detection Of Insulmentioning
confidence: 99%
“…A frequently used dye for fluorescence guiding purposes is IRDye800CW, which has been conjugated to multiple targeting moieties and is increasingly used for clinical FGS in various solid tumor types . We have developed a clinical grade exendin‐4‐IRDye800CW conjugate and shown feasibility of insulinoma targeting and imaging in mice with subcutaneous GLP‐1R overexpressing Chinese hamster lung cell tumors . We intent to start clinical trials in which this tracer is employed for FGS of insulinoma.…”
Section: Imaging Of Insulinoma With Exendin‐4–based Tracersmentioning
confidence: 99%
“…The authors used the FLARE™ imaging system to acquire color video and near-infrared fluorescence images. Later, other suggestions were presented: Wada et al ( 58 ) – near-infrared fluorophores T700-F and T700-H; Park et al ( 59 ) – Ox61 for intraoperative imaging of neuroendocrine pancreatic tumors; and Boss et al ( 60 ) – near-infrared fluorophore exendin-4-IRDye 800CW for insulin and CHI. In our opinion, the development and implementation of clinical neuroendocrine intraoperative navigation can not only completely cure a child with CHI-F (and in some cases CHI-A), but also improve the quality of postoperative life for CHI-D patients.…”
Section: Discussion Of the Research Resultsmentioning
confidence: 99%